Fabrication of microchannels in lithium tantalate by selective etching of structures inscribed with a femtosecond laser - Kore Hasse; Daniel Nwatu; Stella Müller; Sergiy Suntsov; Detlef Kip (JPhys Photonics)
Selective etching of material areas modified by femtosecond laser pulses in the volume of lithium tantalate has been applied to produce hollow microchannels. In a fully monolithic approach, microchannels up to 2.5 mm long with cross sections of 2.5 µ m × 20 µ m were etched into the crystal volume at a depth of 430 µ m. The influence of the laser repetition rate, the pulse energy and the writing speed on the etching time and the etching selectivity was investigated as part of a systematic study. Characteristic process parameters, i.e. selectivity and diffusion coefficient were determined by fitting the etch depth versus time using a superdiffusion model. The obtained parameters are suitable for predicting the results of selective etching for certain process parameters, and thus enable the process to be controlled. A similar study was carried out in sapphire for comparison purposes.